2022
DOI: 10.1007/s00262-022-03282-6
|View full text |Cite
|
Sign up to set email alerts
|

PD-1+ mast cell enhanced by PD-1 blocking therapy associated with resistance to immunotherapy

Abstract: Background Programmed cell death protein 1 (PD-1) antibody has been approved for a variety of tumors, but its effective rate is unsatisfactory. New evidence suggests that mast cells are an important component of the tumor microenvironment and are associated with resistance to immunotherapy, but the underlying mechanism is not clear. Methods Bioinformatics analysis of patients with melanoma in TCGA-SKCM and GSE91061 was used to determine the prognostic val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Bioinformatics analysis of patients with melanoma was used to evaluate the prognostic value of mast cells and their association with anti-PD-1 immunotherapy (Li et al 2022 ). Results confirmed that mast cells may be considered as a poor prognostic factor and are associated with resistance to anti-PD-1 immunotherapy.…”
Section: Mast Cells and Resistance To Immunotherapy In Cancermentioning
confidence: 99%
“…Bioinformatics analysis of patients with melanoma was used to evaluate the prognostic value of mast cells and their association with anti-PD-1 immunotherapy (Li et al 2022 ). Results confirmed that mast cells may be considered as a poor prognostic factor and are associated with resistance to anti-PD-1 immunotherapy.…”
Section: Mast Cells and Resistance To Immunotherapy In Cancermentioning
confidence: 99%
“…MCs express inhibitory receptors on the cell surface including Siglecs-6.-7, -8, -9, CD300a and CD300c and both PD-1/PD-L1 [16,17,[57][58][59][60][61][62]. Both CD300 and Siglec family members suppress FcεRI-initiated MC activation-but their role in melanoma biology is underexplored.…”
Section: Immuno-regulatory Receptors On Mast Cellsmentioning
confidence: 99%
“…Numerous studies have sought to define roles for MCs in melanoma progression with conflicting results, depending on the parameters of MC activation evaluated, the stage of melanoma and the model utilized to investigate MC function. Transcriptome and predictive modeling studies link intratumoral MCs with poor prognosis, metastasis, and resistance to co-stimulatory blockade [7,[12][13][14][15][16][17]. Reduced metastasis has consistently been reported in mouse models in which melanomas are intravenously transplanted into mice fully deficient in MCs (Kit Wsh/Wsh ), or mice in which connective tissue type MCs are constitutively or transiently depleted [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Their use, or use of other clinically administered or tested MC-targeting drugs (anti-Siglec therapies [ 119 ] or other biologics [ 115 ]), could in combination with other cancer treatment modalities (i.e., chemotherapy or immunotherapy) then indeed represent a new promising treatment strategy in which MCs would be approached as inhibitory immune checkpoint cells in the tumor microenvironment [ 113 , 114 ]. This therapeutic approach would be presumably relevant in tumors where the tumor burden with MCs or their products are largely and convincingly associated with the disease severity and dismal prognosis [ 120 , 121 ], or where another therapeutic modality increases their numbers with pro-tumorigenic activities and causes a resistance to the therapy [ 122 ].…”
Section: Mcs In Immunotherapy Of Solid Tumorsmentioning
confidence: 99%
“…Using MCs in combination with DCs in cancer immunotherapy needs to be designed with respect to tumor types, ongoing therapy, and mast cell-driven co-morbidities. The tumors that are known to be more sinister when large numbers of MCs infiltrate them [ 179 ] or when immunotherapy enhances their numbers alongside the growing tumor resistance [ 122 ] are presumably situations where MCs activities need to be suppressed or the cells even eliminated. A similar approach needs to be also considered when patients suffer from diseases related to dysregulated MC numbers [ 180 ] or their activation [ 181 ] or when MCs are directly part of the malignant neoplastic disease [ 182 ].…”
Section: Future Perspectivesmentioning
confidence: 99%